Sludge cake and biofilm formation as valuable tools in wastewater treatment by coupling Integrated Fixed-film Activated Sludge (IFAS) with Self Forming Dynamic Membrane BioReactors (SFD-MBR). (November 2018) - Vergine, Pompilio; Salerno, Carlo; Berardi, Giovanni; Pollice, Alfieri
Highlights: Sludge cake acts as key actor of filtration in SFD-MBR for wastewater treatment. IFAS integration decreased the excess sludge and enhanced denitrification. The presence of carriers increased the frequency of mesh clogging. Both SFD-MBRs showed performance comparable to MBR in same operating conditions. Abstract: Two lab-scale Self Forming Dynamic Membrane BioReactors (SFD-MBR), equipped with 50 µm nylon meshes were set up and operated for the treatment of real municipal wastewater. Plastic carriers were added in one of the two bioreactors to generate a combination of the Integrated Fixed-film Activated Sludge (IFAS) and the SFD-MBR technologies. Overall, the two systems performed very well, achieving excellent effluent quality under steady state conditions and showing good resilience to extreme organic loading conditions. Continuous air scouring and periodical mesh cleaning by jet rinsing with tap water were effective in maintaining stable and high productivity (membrane flux around 67 L m 2  h −1 ) over a period of 140 days. The application of the IFAS process resulted in lower production of excess sludge and improved denitrification. On the other hand, under the tested conditions the combined IFAS-SFD-MBR showed a higher tendency to mesh clogging with respect to the SFD-MBR.